New cave-dwelling huntsman spider species of the genus Sinopoda (Araneae: Sparassidae) from southern China - Liu, Jie; Li, Shuqiang; Jäger, Peter (Zootaxa, 2008)
Nine new species of the genus Sinopoda, collected from Yunnan-Guizhou Plateau and Hainan Island of southern China, are described: Sinopoda anguina sp. nov., Sinopoda crassa sp. nov., Sinopoda fornicata sp. nov., Sinopoda grandispinosa sp. nov., Sinopoda nuda sp. nov., Sinopoda semicirculata sp. nov., Sinopoda triangula sp. nov., Sinopoda undata sp. nov. and Sinopoda yaojingensis sp. nov. The type specimen of Sinopoda longshan Yin, Peng, Yan & Bao 2000 is redescribed and illustrated. All nine new species were collected from caves. The type specimens of new species are deposited in the Institute of Zoology, Chinese Academy of Sciences in Beijing (IZCAS) and Research Institute Senckenberg in Frankfurt am Main (SMF).